EFFECT OF DILUTION, TEMPERATURE AND pH ON THE LYSIS ACTIVITY OF T4 PHAGE AGAINST E.COLI BL21 - M. K. Taj; J. X. Ling; L. L. Bing; Z. Qi; I. Taj; T. M. Hassani; Z. Samreen; W. Yunlin⃰ (Journal of Animal and Plant Sciences, 2014)
The effect of various “range” of dilution, temperature and pH on T4 bacteriophage lytic activity against Escherichia coli had been characterized. Results showed that T4 bacteriophage did lysis from 10-1 to 10-7 dilutions, while no lysis at dilutions 10-8 to 10-10. The yield of T4 bacteriophage is highly dependent upon temperature. Low temperatures of 4°C did not permit T4 bacteriophage to perform lysis on host. While at 15°C, 25°C and 30°C there has been lysis but with little delay. Similarly at thermophilic temperature 41°C T4 bacteriophage developed and performed lysis on its host but at temperature regimes of 45°C, 55°C and 70°C, the T4 bacteriophage was completely inactive.  The ideal temperature for T4 bacteriolytic activity was 37°C. pH of media was also found affecting virus survival indirectly by influencing extent of virus adsorption to other particles and surfaces and T4 bacteriophage was stable in pH range from 4 to 10. Our study demonstrates that apart from ideal values of respective parameters previously been demonstrated, the lytic activity of T4 bacteriophage is maximal at various other values of temperature, pH and dilution, which can broaden the spectrum of application of phage therapy.
Keywords: T4 Phage; E coli; Dilution; Temperature; pH